2017
DOI: 10.1080/02713683.2016.1256414
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Antimicrobial Activity:In VitroAnalysis after Topical 0.5% Chloramphenicol Application

Abstract: Aqueous humor displayed no bactericidal effect against any of the microorganisms evaluated after topical 0.5% chloramphenicol application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[14][15][16][17][18][19][20][21] These studies were often correlated with the definition of therapeutic capabilities of the different compounds to optimise their use and promote a correct therapeutic attitude. 15,[22][23][24] Our results suggest that high concentrations in the eye drops are required to significantly change the concentration of hydrocortisone in the anterior chamber. Even if the complications or adverse effects related to both the low-and high-concentration treatments were not studied, we can suggest that eye drops with a low concentration of hydrocortisone could represent an adequate and safe option for a prolonged treatment in those conditions when we can observe a mild-to-moderate chronic ocular surface inflammation associated with lacrimal tears alteration, as dry eye disease or after routine cataract surgery, as their administration does not appear to change the anterior chamber concentration of hydrocortisone.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21] These studies were often correlated with the definition of therapeutic capabilities of the different compounds to optimise their use and promote a correct therapeutic attitude. 15,[22][23][24] Our results suggest that high concentrations in the eye drops are required to significantly change the concentration of hydrocortisone in the anterior chamber. Even if the complications or adverse effects related to both the low-and high-concentration treatments were not studied, we can suggest that eye drops with a low concentration of hydrocortisone could represent an adequate and safe option for a prolonged treatment in those conditions when we can observe a mild-to-moderate chronic ocular surface inflammation associated with lacrimal tears alteration, as dry eye disease or after routine cataract surgery, as their administration does not appear to change the anterior chamber concentration of hydrocortisone.…”
Section: Discussionmentioning
confidence: 73%
“…These studies were often correlated with the definition of therapeutic capabilities of the different compounds to optimise their use and promote a correct therapeutic attitude. 15 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Also, in the postoperative period it has to maintain its impermeability avoiding the wound leak and reducing the endophthalmitis risks. In fact, it has widely shown that during a postoperative wound leak the efficacy of topical or systemic antibiotics in controlling an eventual postoperative bacterial infection is reduced [8,9,10]. It has been shown that during the cataract surgery an increase of the main wound width can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that during the cataract surgery an increase of the main wound width can be induced. [8,9]. Some authors suggested that corneal incision enlargement was due to instrument manipulation.…”
Section: Discussionmentioning
confidence: 99%